METHODOLOGICAL PROBLEMS OF HIGHER SCHOOL DIDACTICS - G. I. Ibragimov (Образование и наука)
The aim of the research is to identify the concept of vocational didactics and specificity of learning process along with its components in the context of global implementation of information technologies and competenceoriented educational requirements.The research methods include the analysis and synthesis of pedagogical materials and innovative experience of vocational education, abstraction methods, and modeling.The author specifies didactics as a subdivision of pedagogy investigating the learning process and development of personal life experience – i.e. the complex of knowledge, skills and behavior patterns. Accordingly, professional didactics deals with developing personal life experience as a complex of scientific and professional knowledge, skills and behavior patterns. The emphasis is on students’ personal learning activity, whereas a teacher is to design and implement all the didactic means (forms, methods, tools) and conditions facilitating students’ experience formation. In addition, the author identifies the essential features of learning process in the context of information technologies implementation in educational process.The research findings can be implemented by experts in didactics while devising educational techniques oriented on developing students’ personal experience in learning process.